2021
DOI: 10.1108/aia-12-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

The presentation, recognition and diagnosis of autism in women and girls

Abstract: Purpose Autistic women and girls have received comparatively less attention within clinical practice and research. Research suggests women tend to be diagnosed later than men, and are more likely to experience misdiagnosis. Design/methodology/approach This paper aims to report a narrative literature review that examines research on the presentation, recognition, and diagnosis of autistic women and girls. Findings Findings suggest that autistic females present differently to males and highlight low recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…We refer the reader to a review by Driver and Chester [20], and references therein, who summarise many of the clinical issues regarding autism in females. We will highlight some of these aspects here but with a focus on possible reasons for the differences and on autism in females with a non-syndromic intellectual disability.…”
Section: Explaining the Difference Between The Sexesmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer the reader to a review by Driver and Chester [20], and references therein, who summarise many of the clinical issues regarding autism in females. We will highlight some of these aspects here but with a focus on possible reasons for the differences and on autism in females with a non-syndromic intellectual disability.…”
Section: Explaining the Difference Between The Sexesmentioning
confidence: 99%
“…Nonetheless, clinicians can help in better diagnosing females by dismissing the notion of autism as a male disorder and not dismissing concerns of parents. A clinician also needs to make sure that behind the mental illness diagnosis being made of a patient, there may be autism [20].…”
Section: Diagnosis In Womenmentioning
confidence: 99%
“… 3 , 4 Indeed, examining the role of gender in diagnostic instruments, studies have found that most of the diagnostic tools used currently were developed based largely on the observation of boys, and that many diagnostic tools, including the Autism Diagnostic Observation Schedule (ADOS) and Autism Diagnostic Interview-Revised (ADI-R), are less sensitive to women and girls. 5 Others have found six traits and behaviours which consistently show gender differences, and which are a barrier to young autistic women gaining an autism diagnosis: behavioural problems, social and communication abilities, additional diagnoses/misdiagnosis, relationships, language, and repetitive and restrictive behaviours and interests. 6 Driver and Chester 5 support this, showing that many autistic women are first mis/diagnosed with mental health conditions, overshadowing an underlying autism diagnosis and stopping further investigation.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Others have found six traits and behaviours which consistently show gender differences, and which are a barrier to young autistic women gaining an autism diagnosis: behavioural problems, social and communication abilities, additional diagnoses/misdiagnosis, relationships, language, and repetitive and restrictive behaviours and interests. 6 Driver and Chester 5 support this, showing that many autistic women are first mis/diagnosed with mental health conditions, overshadowing an underlying autism diagnosis and stopping further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation